Memória e representação em Barra do Garças: o conflito na Aldeia Meruri - Silva, Phábio Rocha da (2012)
This research approach the resistance of the people of Barra do Garças in relation to indigenous people that live in the region project .With the internalization of Brazil - Marching westward, the city of Barra do Garças and region receives a large flow of migration, entering a number of complications in the occupation of that territory inserting a series of complications in land use and the resulting struggle for dominance of the land The discussions started with the analysis of category memory and representation, and study how the conflict occurred in the village Meruri on July 15, 1976 and its effects on the representation of the "other." Besides the observation reports of some students Basic Education about their perceptions of the presence of the Indian city. In our view the memories of conflicts in the region between Indians and no indigenous, served as the basis to justify the current resistance to indigenous groups in Barra do Garças therefore memory borrowed from others, withheld facts that justify this position.